2022
DOI: 10.1049/rpg2.12541
|View full text |Cite
|
Sign up to set email alerts
|

Analytical reliability evaluation method of smart micro‐grids considering the cyber failures and information transmission system faults

Abstract: The reliability of smart micro‐grids (SMGs), as a cyber‐physical system (CPS), might be influenced by cyber failures and information transmission faults. Several Monte Carlo simulation (MCS)‐based approaches have been reported to assess the reliability of SMGs and smart grids. On the other hand, analytical reliability assessment methods have been presented in some research works, while the cyber system has not been concerned. However, the literature shows a research gap in developing an accurate and fast relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Research by [93] confirmed that cyber failures and information transmission faults lead to an occurrence of 5.7 % expected energy not supplied (EENS) error. Moreover, inapt CNC configuration generated up to 70 MW EENS per year [88].…”
Section: Degradation Valuementioning
confidence: 95%
See 2 more Smart Citations
“…Research by [93] confirmed that cyber failures and information transmission faults lead to an occurrence of 5.7 % expected energy not supplied (EENS) error. Moreover, inapt CNC configuration generated up to 70 MW EENS per year [88].…”
Section: Degradation Valuementioning
confidence: 95%
“…Whether it is an instant impact, such as the immediate failure of the equipment or is long deteriorated system, such as mishandling the worn-out component [92]. From outside the microgrid, the long-distance operator sometimes causes a ruckus in the cyber setting of the microgrid and disturbs the transmission line or distribution network [93] [94]. The last significant impact comes from the policy sector, whether it is concerning the policy at the beginning of the microgrid project or the ongoing policy for the continuous operation of the microgrid [95][96] [97].…”
Section: Other Performance Reduction Factormentioning
confidence: 99%
See 1 more Smart Citation
“…The MCS‐based reliability assessment methods are precise [9, 10]. However, they are not adequately fast [11]. Hence, they cannot be effectively used in developing reliability improvement strategies, particularly if evolutionary algorithms are used [12].…”
Section: Introductionmentioning
confidence: 99%
“…The precise models have been reported based on MCS for SGs’ reliability evaluation. However, there are some challenges to MCS‐based methods of SGs’ reliability evaluation [11]. The challenges regarding execution time and speed of such approaches limit their applications for real‐time operational decisions and optimal design and planning for SGs, using metaheuristic algorithms.…”
Section: Introductionmentioning
confidence: 99%